The relationship between directional components of dynamic response and maximum principal strain for impacts to an American football helmet. (September 2020) - Taylor, Karen; Hoshizaki, T Blaine; Post, Andrew; Gilchrist, Michael D
Impact parameters used to design the American football helmet and the parameters associated with mechanisms of concussive injury are not consistent. Head impacts resulting in concussive injury in football are characterized as events creating rotational motion of the head that generate brain tissue strain. The extent of tissue strain influences the resulting severity of injury. Helmet technology aimed to decrease brain tissue strain by reducing the extent of brain motion could help reduce injury risk. Current helmet performance and evaluation measures, such as peak resultant of linear and rotational acceleration, do not fully define directional brain motion and therefore cannot provide sufficient information for this type of improvement. This study was conducted to determine whether coordinate components (X, Y, and Z) of linear and rotational acceleration would correlate with maximum principal strain, a common measure of brain injury risk. Coordinate components define directional motion of the head and offer a specific design parameter more easily reduced using engineered structures than peak resultant acceleration. In addition to coordinate components, this study introduces the dominant component, defined as the coordinate component with the highest contribution to the resultant acceleration, for additional evaluation. The results show that the relationship between the X, Y, and Z coordinate components of acceleration and maximum principal strain is location- and direction-dependent. The study indicates a strong relationship between the peak resultant and dominant components of acceleration to maximum principal strain. Because the dominant component of acceleration accounts for direction and location, identifying the relationship between dominant acceleration and maximum principal strain demonstrates the potential use of this metric to improve future helmet innovation aimed at reducing tissue strain.